2016
DOI: 10.4330/wjc.v8.i12.728
|View full text |Cite
|
Sign up to set email alerts
|

Newer perspectives of coronary artery disease in young

Abstract: Coronary artery disease (CAD) occurring in less than 45 years of age is termed as young CAD. Recent studies show a prevalence of 1.2% of CAD cases in this age group. Ethnic wise south Asians especially Indians are more vulnerable to have CAD in young age group with a prevalence of 5% to 10%. Conventional risk factors such as smoking, diabetes, hypertension, obesity and family history seems to be as important as in older CAD subjects. But the prevalence of these risk factors seems to vary in younger subjects. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 76 publications
8
96
2
5
Order By: Relevance
“…A cohort of more than 1,000 patients with newly diagnosed CAD was selected, thus allowing an in-depth evaluation of any relevant difference between younger and older patients. In accordance with previous studies [4, 6], younger CAD patients were found to be more frequently males, active smokers, obese, with higher levels of LDL cholesterol, and lower functional capacity. Besides, these younger subjects were also less likely to be treated with statins and aspirin at the time of coronary angiography.…”
supporting
confidence: 78%
“…A cohort of more than 1,000 patients with newly diagnosed CAD was selected, thus allowing an in-depth evaluation of any relevant difference between younger and older patients. In accordance with previous studies [4, 6], younger CAD patients were found to be more frequently males, active smokers, obese, with higher levels of LDL cholesterol, and lower functional capacity. Besides, these younger subjects were also less likely to be treated with statins and aspirin at the time of coronary angiography.…”
supporting
confidence: 78%
“…However, report on the association between hypertension and TB in young STEMI patients remains scanty. Previous study found that the prevalence of hypertension was 25% in young CAD patients as compared with 13% in comparable age group without CAD, and the prevalence of hypertension was much higher in elderly CAD individuals as compared with young CAD patients . Several studies also reported an increasing trend of the prevalence of hypertension in young CAD patients .…”
Section: Discussionmentioning
confidence: 94%
“…Previous study found that the prevalence of hypertension was 25% in young CAD patients as compared with 13% in comparable age group without CAD, and the prevalence of hypertension was much higher in elderly CAD individuals as compared with young CAD patients. 36 Several studies also reported an increasing trend of the prevalence of hypertension in young CAD patients. 36,37 Our results indicate that the prevalence of hypertension is significantly higher in patients with HTB than in patients with LTB (75.0 vs. 17.1%, P < 0.001).…”
Section: Determinants Of High Tb In Young Chinese Stemi Patientsmentioning
confidence: 94%
“…Hypertension is one of the leading causes of PCAD and death . In the study conducted by Aggarwal et al, the prevalence of hypertension was higher in young CAD patients (25%) compared to individuals without CAD (13%) . In a study on Indian population, hypertension was identified as a modifiable risk factor for inpatients younger than 55 years of age with heart disease.…”
Section: Discussionmentioning
confidence: 99%